Shopee Affiliate Marketing in Islamic Business Ethics Perspective - Salma, Adilah; Shely Intan Agvela; Muhibban (Sharia Business Management Department of STEBIS Bina Mandiri, 2024)
This journal aims to find out how the shopee affiliate marketing model according to the perspective of Islamic business ethics. The method used is a normative perspective approach that focuses based on certain norms, moral values, or ethical standards. The results that have been obtained from this are that shopee affiliates have applied the principles of Islamic business ethics. From this shopee affiliate program, there are many positive influences on the community to continue to develop business through the shopee marketplace.